Estilos de Aprendizaje y su influencia en el Rendimiento Académico en estudiantes de la UAN Ibagué (2020)
The objective of this research was to establish the relationship between learning styles (EA) and their influence on academic performance (RA). For the development of this project, there was a sample of 120 students; who answered the CAMEA40 instrument, at the same time, the paradigm used was the empirical-analytical, positivist one, because it is based on the verification of the results of the investigation that, together with empirical logic and observation, allows us to identify the styles of learning present in students. T